Seton in Treating ComplexAnorectal Fistula-Our Experience (Journal of Surgical Sciences, 2019)
Background : Complex anorectal fistula may be endowed by the level at which the primary tract crosses the sphincters, the presence of secondary extensions or the difficulties faced in the treatment. Existing different treatment modalities like local advancement flap, LIFT procedure, fistulotomy and use of seton. Surgeons are afraid of incontinence in treating complex anorectal fistula. The aim of treatment of anal fistula is to cure the disease avoiding faecal incontinence. Among different procedures, Seton, a thread of foreign material, passed through the fistulous track and encircling sphincter mass thereby severing the muscle gradually without allowing it to spring apart and replacing the cut by the line of fibrosis thus avoiding incontinence, is an acceptable method practiced world wide. The purpose of the study is to evaluate and share our experience with others about the result of using seton in the treatment of complex anal fistula in our setting.Method: Between January 2003 and December 2008, I have taken the 1st 100 patients underwent surgery for complex anal fistula in Colorectal Surgery Unit of Bangabandhu Sheikh Mujib Medial University, Dhaka. It involved initial identification and partial laying open of the fistulous tract. A tight seton is placed around the external sphincter and is not removed until the internal orifice has migrated towards the perianal skin.Results: Out of 100 patients with mean age 43 years (range 19-65 years) 6 female and rest male underwent the procedure of seton. The median follow-up was 28.6 (24-36) months. The mean time of wound healing was 9.5 weeks (range 6-15). Recurrence occurred in two patient (2%). Continence disorders of flatus and loose stool were noted in 14 patients (14%). The duration with the seton in place was 56 days (range 20-190).Conclusion: The technique shows excellent results in the treatment of complex anal fistulous with preservation of faecal continence.Journal of Surgical Sciences (2013) Vol. 17 (1) : 14-17